PENGARUH MODEL PEMBELAJARAN CONNECTED MATHEMATIC PROJECT TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS - Sutiana, Nana (STKIP YPM Bangko, 2019)
This research aims to describe the ability of mathematical representation using the learning model of the connected mathematic project better than conventional learning. The research method used is the experimental method with a quantitative approach using a posttest-only control design design with a population of class IX students totaling 3 classes. The sampling technique uses simple random sampling, selected class IX A as the experimental class and class IX B as the control class. Data collection uses test techniques with instruments in the form of problem descriptions. The results of data analysis show that the value of tcount > ttable means that the ability of mathematical representation using the connected mathematic project learning model is better than conventional learning.